G protein-regulated endocytic trafficking of adenylyl cyclase type 9 - André M Lazar; Roshanak Irannejad; Tanya A Baldwin; Aparna B Sundaram; J Silvio Gutkind; Asuka Inoue; Carmen W Dessauer; Mark Von Zastrow (eLife, 2020)
GPCRs are increasingly recognized to initiate signaling via heterotrimeric G proteins as they move through the endocytic network, but little is known about how relevant G protein effectors are localized. Here we report selective trafficking of adenylyl cyclase type 9 (AC9) from the plasma membrane to endosomes while adenylyl cyclase type 1 (AC1) remains in the plasma membrane, and stimulation of AC9 trafficking by ligand-induced activation of Gs-coupled GPCRs. AC9 transits a similar, dynamin-dependent early endocytic pathway as ligand-activated GPCRs. However, unlike GPCR traffic control which requires β-arrestin but not Gs, AC9 traffic control requires Gs but not β-arrestin. We also show that AC9, but not AC1, mediates cAMP production stimulated by endogenous receptor activation in endosomes. These results reveal dynamic and isoform-specific trafficking of adenylyl cyclase in the endocytic network, and a discrete role of a heterotrimeric G protein in regulating the subcellular distribution of a relevant effector.